The efficacy of picture vs. word danger cues in reducing imitation of dangerous actions in children - Dong, Shuanglong; Zhao, Liang; Bian, Zhaobin; Wang, Yansong (Frontiers in Psychology, 2024)
Children are known for their strong curiosity and limited self-control, which often leads them to imitate the actions of others, regardless of whether those actions are safe or dangerous. This study investigated whether providing dangerous cues to children can effectively inhibit their imitation of dangerous behaviors. Additionally, it compared the efficacy of picture cues versus word cues in reducing the tendency to imitate dangerous actions. In the experiment, all participants observed an agent grasping an object and were instructed to perform a corresponding keystroke response when a number appeared. The 76 child participants were divided into two groups: one group received word cues, while the other group received picture cues. A comparable number of adults were also included in the study for reference purposes. The findings reveal that picture cues, as opposed to word cues, significantly aid in reducing children’s propensity to imitate dangerous actions. This suggests that picture cues are more effective than word cues in mitigating the imitation of risky behaviors among children. These insights have important implications for enhancing children’s safety education and preventing accidents by utilizing more effective visual danger cues.